Das Verwaltungsrecht der Vereinigten Staaten von Amerika - Schmidt-Aßmann, Eberhard (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
US administrative law forms a body of law that is considered to be particularly ‘political’. From an early stage on, US administrative law has endeavoured to provide instruments and procedures that foster and implement democratic ideals and concepts; consequently, US ‘freedom of information’ and the standards of public participation in the rulemaking process have often served as a model for foreign administrative law systems. Nevertheless, the agency actions have constantly been questioned and disputed. This book offers a systematic analysis of the constitutional foundations as well as the procedures, of liability and judicial review in administrative matters, and it examines the legitimacy of the American ‘administrative state’.